SISTEM INFORMASI PENGELOLAAN ARSIP SURAT MASUK DAN KELUAR MENGGUNAKAN PHP MYSQL PADA BADAN KESATUAN BANGSA DAN POLITIK - Ridla, Muhammad Ali; Istiqomah, Nurul (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2025)
There is a large number of incoming and outgoing letters from the Banyuwangi National Unity and Political Agency's workplace, so currently there is a need for a system that can help with performance related to using correspondence. So it is necessary to design an information system for managing mail records. Mail archiving means records of incoming and outgoing letters that are received as well as those that are sent. At this time, the mechanism implemented in the management of incoming and outgoing letters at the National Unity Agency and Noble Politics workplaces as long as the receipt, creation, storage and documentation of letters are all carried out conventionally. Using a mail archive management information gadget can reduce difficulties and time spent searching for mail information and facts, and improve the management of existing mail archives. This mail archive management information tool was created using PHP Hypertext Preprocessor (personal home page) and MySQL for database processing. What is obtained from this research means creating a news machine that can manage incoming and outgoing mail according to a specified flow, and can solve current problems.